EFFECTS OF ETHANOL EXTRACT OF RADIX SOPHORAE FLAVESCENTIS ON ACTIVITY OF COLON CANCER HT29 CELLS - XIAO, Zhi-Ming; WANG, Ai-Min; WANG, Xiao-Yan; SHEN, Shou-Rong (African Journal of Traditional, Complementary and Alternative Medicines, 2013)
This paper mainly studied the inhibitory effect of total ethanol extract of Radix Sophorae Flavescentis on proliferation of colon cancer HT29 cells. By reflux extraction method and with ethanol as extraction solvent, different extracts were obtained at different ethanol concentrations, different solid-liquid ratios, and at different times. And their inhibitory activities against HT29 cells were compared using MTT assay. The experimental results showed that the extraction processes under three conditions can all draw relatively high inhibition rates. The optimum ethanol extraction process conditions were as follows: a solid-liquid ratio of 1:9, 80 min of heat reflux extraction with 95% ethanol.